Strengthening Character Values with 'Unconditional Love' as the Energy of Eternal Happiness: The Perspective of Pancasila and Psychology - Martina Sudibja; A. Juntika Nurihsan; Encep Syarief Nurdin; Asep Dahliyana; Bunyamin Maftuh; Yadi Ruyadi (The Indonesian Institute of Science and Technology Research, 2026)
Unconditional love is increasingly recognized as a fundamental value that promotes psychological well-being, social harmony, and character development. However, limited research has examined its role as a psychosocial resource for sustaining happiness within the cultural and philosophical framework of Pancasila. This study explores how unconditional love functions as a character value and a source of enduring happiness from the perspectives of indigenous psychology and Pancasila values in Indonesia. A qualitative case study design was employed. Data were collected through semi-structured interviews with 20 families from diverse professional backgrounds in Bandung City and supported by longitudinal counselling case studies. Data were analyzed using thematic analysis with source triangulation and member checking to enhance trustworthiness. The findings identify three interconnected dimensions of unconditional love: acceptance, respect, and genuine care. These dimensions foster emotional resilience, psychological security, harmonious family relationships, and spiritual balance. Participants reported that practicing unconditional love reduced interpersonal conflict, strengthened empathy, and promoted sustainable happiness. The findings further indicate that unconditional love facilitates the internalization of core Pancasila values, particularly just and civilized humanity, national unity, and social solidarity. As a culturally embedded psychosocial resource, unconditional love supports both individual and family well-being while encouraging positive character development. This study contributes to indigenous psychology by demonstrating that unconditional love bridges psychological well-being and Pancasila-based moral development. Integrating unconditional love into character education and family-based interventions may strengthen personal flourishing, social cohesion, and sustainable well-being in contemporary Indonesian society.